Study on mechanical properties and microstructure of soil-cement solidified recycled aggregate concrete using bridge demolition waste - Yang Du; Ziqing Cheng; Peichen Cai; Ke Lou; Shaodong Wei; Xiaoyu Wang; Shengjie Wang; Xuesong Mao; Feiheng Huang; Qian Wu (PLoS ONE, 2026)
This study investigates the mechanical behavior and microstructural characteristics of recycled aggregate concrete (RAC) solidified with soil cement, using high-quality recycled aggregates derived from demolished reinforced-concrete bridges. Concrete mixtures were prepared with varying recycled aggregate replacement ratios (60%, 80%, 100%) and soil-cement contents (15%, 18%, 21%). Compressive strength (CS) tests and scanning electron microscopy (SEM) analyses were conducted. Owing to the dense and high-strength nature of bridge-demolition aggregates, increasing the recycled aggregate replacement ratio from 60% to 100% led to a noticeable improvement in compressive strength—an outcome that contrasts with most studies using lower-grade construction waste. The results showed that increasing the soil-cement content raised the 28-day CS to a maximum of 21 MPa. The 7-day CS exceeding 70% of the 28-day value, indicating rapid early strength development. Compared with conventional concrete, the RAC incorporating bridge-derived aggregates demonstrated enhanced crack resistance and a denser microstructure. A regression model relating mix parameters and curing age to CS achieved coefficients of determination exceeding R 2 = 0.99, demonstrating its strong predictive capability. SEM observations showed progressive pore refinement and matrix densification during curing, consistent with the measured strength gains. These findings support the engineering application of RAC and promote the sustainable reuse of construction waste in infrastructure projects.